2014
DOI: 10.1186/1477-7525-12-2
|View full text |Cite
|
Sign up to set email alerts
|

Falls and EQ-5D rated quality of life in community-dwelling seniors with concurrent chronic diseases: a cross-sectional study

Abstract: BackgroundAlthough recommended for use in studies investigating falls in the elderly, the European Quality of Life Group instrument, EQ-5D, has not been widely used to assess the impact of falls on quality of life. The aim of this study was to investigate the association of single and frequent falls with EQ-5D rated quality of life in a sample of German community-dwelling seniors in primary care suffering a variety of concurrent chronic diseases and conditions.MethodsIn a cross-sectional study, a sample of com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
51
4
7

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(67 citation statements)
references
References 42 publications
4
51
4
7
Order By: Relevance
“…Fall can cause adverse physical consequences such as fractures, restriction of active ability, deterioration of health, and decreased physical activity as well as reduced psychosocial consequences such as social isolation, low mode, and risk of institutionalization [7, 8]. Moreover, fall would have an important impact on subsequent disability, quality of life, and mortality [9, 10]. …”
Section: Introductionmentioning
confidence: 99%
“…Fall can cause adverse physical consequences such as fractures, restriction of active ability, deterioration of health, and decreased physical activity as well as reduced psychosocial consequences such as social isolation, low mode, and risk of institutionalization [7, 8]. Moreover, fall would have an important impact on subsequent disability, quality of life, and mortality [9, 10]. …”
Section: Introductionmentioning
confidence: 99%
“…More than 30% of older adults aged 65 years and older and 50% of older adults aged 80 years and older fall each year (Stevens and Sogolow, 2008; Hammer, 2010; Soriano et al, 2007). Falls have a significant impact on subsequent disability, quality of life, and mortality (Finlayson and Peterson, 2010; Centers for Disease Control and Prevention and National Center for Injury Prevention and Control, 2014; Thiem et al, 2014). Older adults who fall once are two to three times more likely to fall again within the next six months (Stevens and Sogolow, 2008).…”
mentioning
confidence: 99%
“…Although this is the first large study evaluating the impact of falls on quality of life in older cancer survivors, the results follow a similar pattern demonstrated in prior studies in the general elderly population. 14,15,24 A recent study of community-dwelling Medicare beneficiaries without cancer reported a negative impact of falls on the PCS (−5.57 points) as well as the MCS (−3.08 points) of the VR-12 health survey. 15 Moreover, the longitudinal decline in the HRQOL scores following falls are also similar to those reported in a prospective study in the general elderly population which showed a decline in follow-up SF-12 PCS and MCS scores suggesting that falls have negative physical as well as psychological impact.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies in older populations without cancer have shown a “dose-response” relationship between number of falls and HRQOL in which two or more falls are associated with greater decline compared to one fall. 24 Categories of cancer-specific variables available in this database such as cancer type, stage, time since diagnosis may not have enough detail to fully capture the impact of cancer on HRQOL. More detailed staging and treatment history (including chemotherapy type) should be included in future research evaluating association of falls with outcomes of older patients with cancer.…”
Section: Discussionmentioning
confidence: 99%